Peran Alokasi Dana Desa (ADD) Dalam Mengentaskan Kemiskinan Guna Memajukan Perekonomian Masyarakat Desa Kwala Besilam Kecamatan Padang Tualang Kabupaten Langkat - Lestya Puji Atmazah, Azhar, Khairani Sakdiah (CV. PUSDIKRA MITRA JAYA, 2023)
This study focuses on discussing the Role of Village Fund Allocation (ADD) in Alleviating Poverty in order to Advance the Economy of the Community of Kwala Besilam Village, Padang Tualang District, Langkat Regency and the factors that influence it and then reviewed according to Islamic economics. The research method used in this study is a descriptive qualitative research method with an empirical approach. The informants in this study were related village government officials. The results of the study explain that the use of Village Fund Allocations in the village of Kwala Besilam has been properly used in accordance with the applicable law. The infrastructure includes community walkways, agricultural paths, siring and hamlet connecting bridges, while the empowerment is in the form of empowering mat crafts, hood crafts, rago crafts, and chicken coop crafts managed by the women of Kwala Besilam Village, Padang Tualang District, Langkat Regency. Factors supporting the management of Village Fund Allocation (ADD) in advancing the community's economy in Kwala Besilam, Padang Tualang District, Langkat Regency are policy support from the local government, quality human resources, community participation strongly supports this activity by carrying it out in mutual cooperation to advance village development more advanced. Meanwhile, the inhibiting factors in managing the Village Fund Allocation (ADD) in advancing the community's economy in Kwala Besilam, Padang Tualang District, Langkat Regency are the Low Synchronization Between Planning at the Village and District Levels, the amount of Village Fund Allocations (ADD), and the lack of intensity of outreach. According to Islam, the role of the Village Fund Allocation (ADD) used for infrastructure and economic empowerment is appropriate, because both infrastructure development and economic empowerment are for the benefit of the community, namely to increase the economy and quality of life for the community in Kwala Besilam Village, Padang Tualang District, Langkat Regency.